PENGARUH INVESTASI SEKTOR PERTANIAN DAN INDUSTRI PENGOLAHAN HASIL PERTANIAN DI PROVINSI SULAWESI TENGAH - Rustam Abd. Rauf; Arief Daryanto; Sjafri Mangkuprawira; D. S. Priyarsono (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
This research aims to analyze the agricultural and agricultural industrial processing sectors which contribute highest role based on input and output market transaction mechanism. The finding showed that the degree of sensitivity index was less than one (0.7678). Similarly, the index of backward linkages for agricultural sector on industries and services was also less than one (0.9199). This finding indicates that the agricultural sector has not yet either used output from other sectors or push investment decisions to use its output. The same finding has also been occured for its supply for input.